Work related risk factors for lower back pain among nurses in Ahmadu Bello University Teaching Hospital (ABUTH), Zaria-Nigeria - Muhammed, Awwal Farooq; Ladan, Awwal M.; Musa, Halima Abdul; Garba, Abdullahi Mustapha (International Organization of Scientific Research, 2015)
This study was carried out to assess the work-related risk factors for Lower Back Pain (LBP) among nurses in Ahmadu Bello University Teaching Hospital (ABUTH), Shika - Zaria. The main objective of this Study is to determine the prevalence and duration of LBP as well as to identify the work-related risk factors associated with low back pain (LBP) among Nurses in ABUTH. This Study also examines the relationship between Socio-demographic characteristics of Nurses in ABUTH and development of LBP. The descriptive survey design was adopted and data were collected with help of pre-established Questionnaires. Multi-stage sampling method was used among nurses working in various departments/ units of the hospital. The Study sampled 120 Nurses of which 98 fully participated and filled the questionnaires completely. The major findings of this study were as follows: The cumulative point-prevalence of LBP among nurses was 82.7%. The duration of LBP among nurses were noted to be highest among those in pain for within 3 weeks (69.1%), this is followed by those whose pain is more than 12 weeks (12.3%). Risk factors associated with LBP were highest in lifting of patients or objects (90%), standing on duty (88.9%) and moving of heavy objects/equipments (81.5%). Furthermore, there were significant relationship between LBP and gender (X2 =3.77), and then LBP and Nurses’ Ward/Unit of work (X2 = 11.754). Therefore, it is recommended that efforts be made to prevent lower back pain among nurses working in ABUTH by implementing preventive measures using a multi-dimensional approach such as Sensitizing and encouraging nurses about using safe handling techniques while at work through workshops and use of posters, Training and providing manual laborers for transferring and lifting of patients, among others.